2020
DOI: 10.1002/zamm.202000231
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Bending, buckling and vibration analyses of FG porous nanobeams resting on Pasternak foundation incorporating surface effects

Abstract: In the current paper, size‐dependent mechanical analysis of functionally graded porous (FGP) nanobeams resting on Pasternak foundation in thermal environment is presented based on nonlocal strain gradient theory and Gurtin‐Murdoch surface elasticity theory. The nanobeam is modeled based on Euler‐Bernoulli beam theory, Timoshenko beam theory and Reddy's third‐order shear deformation theory and the set of the governing equations are solved for a clamped‐clamped FGP nanobeam using generalized differential quadrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…where, T = 0, 0, q, 0, 0 ½ T . Inserting equation ( 13) into equation (19) for e s and then integrating over the top and bottom surfaces for the work due to t 0 give…”
Section: Matrix Representation Of the Energy Functionalmentioning
confidence: 99%
See 1 more Smart Citation
“…where, T = 0, 0, q, 0, 0 ½ T . Inserting equation ( 13) into equation (19) for e s and then integrating over the top and bottom surfaces for the work due to t 0 give…”
Section: Matrix Representation Of the Energy Functionalmentioning
confidence: 99%
“…Gholami et al 18 suggested a multiscale scheme accounting for the geometric and material nonlinearities to investigate the vibrations behavior of embedded graphene sheets with large-amplitude of oscillations. Enayat et al 19 used the nonlocal and Gurtin-Murdoch’s surface theories to do a mechanical analysis of functionally graded porous nanobeams subjected to thermal environment. Abdelrahman and Eltaher 20 presented a comprehensive study to evaluate the static bending and buckling stability of perforated nanobeams with consideration of the surface free energy based on different beam theories.…”
Section: Introductionmentioning
confidence: 99%
“…Enayat et al. [47] modeled dynamically the bending behavior of a nonlocal strain gradient functionally graded porous nanobeams resting on Pasternak foundation in thermal environment based on Euler‐Bernoulli beam theory, Timoshenko beam theory and Reddy's third‐order shear deformation theory.…”
Section: Introductionmentioning
confidence: 99%
“…The influences of the porosity parameter, viscosity of the pore fluid, the velocity of the moving loads, and stiffness of the foundation on the dynamic response of the beam were examined by them. Enayat et al 28 , 29 studied the mechanical buckling, static bending, and free vibration characteristics of porous nanobeams subjected to thermal loading. It was shown by them that by increasing the porosity parameter, the static deflection increases and the critical buckling load decrease; but the effect of the porosity parameter on the natural frequencies significantly depends on the pore distribution pattern.…”
Section: Introductionmentioning
confidence: 99%